Mapping Chondrocyte Viability, Matrix Glycosaminoglycan, and Water Content on the Surface of a Bovine Metatarsophalangeal Joint. (April 2016) - Lin, Yi-Cheng; Hall, Andrew C.; Smith, Innes D. M.; Salter, Donald M.; Simpson, A. Hamish R. W.
Objective: The purpose of this study was to determine if there were variations in chondrocyte viability, matrix glycosaminoglycan (GAG), and water content between different areas of the articular surface of a bovine metatarsophalangeal joint, a common and reliable source of articular cartilage for experimental study, which may compromise the validity of using multiple samples from different sites within the joint. Methods: Nine fresh cadaveric bovine metatarsophalangeal joints were obtained. From each joint, 16 osteochondral explants were taken from 4 facets, yielding a total of 144 cartilage specimens for evaluation of chondrocyte viability, matrix GAG, and water content. A less invasive method for harvesting osteochondral explants and for processing the biopsy for the assessment of chondrocyte viability was developed, which maintained maximal viability within each cartilage explant. Results: There was no significant difference between the 16 biopsy sites from the different areas of the joint surface with respect to chondrocyte viability, matrix GAG and water content. Pooled data of all samples from each joint established the baseline values of chondrocyte viability to be 89.4% ± 3.8%, 94.4% ± 2.2%, and 77.9% ± 7.8%, in the superficial quarter, central half, and deep quarter (with regard to depth from the articular surface), respectively. The matrix GAG content of bovine articular cartilage was 6.06 ± 0.41 μg/mg cartilage, and the cartilage water content was 72.4% ± 1.5%. There were also no significant differences of these 3 variables between the different joints. Conclusion: It is thus reasonable to compare biopsies obtained from different sites, as a biopsy from one site would be considered representative of the whole joint.